RETRACTED : Pengaruh Tata Ruang Kantor Terhadap Kinerja Guru di Madrasah Pembangunan UIN Jakarta - Yuniarti, Dwika; Waruwu, Nurdelima; SAM, Muarif (ARZUSIN, 2022)
This study aims to determine the effect of office layout on teacher performance at Madrasah Pembangunan UIN Jakarta. This type of research is quantitative with a linear regression analysis approach. This study uses probability sampling where the population is MP UIN Jakarta teachers. Of the total 165 sample teachers used in this study 63 teachers from all levels with specifications, 34 MI teachers, 19 MTs teachers, and 10 MA teachers. The research instrument was a questionnaire, document study, and interviews. The questionnaire was used as the main data collection which was distributed to the research subjects, while document study and interviews were used as complementary techniques to obtain data. The research result states that there is a significant influence between the influence of office layout on teacher performance at MP UIN Jakarta. This can be seen from the data processing results of the calculation of SPSS ver 23, through statistical testing of the T-test. The results of the T-test value are 6.140 and T-table is 1.999 with a significance of 0.000. Using the test criteria T-count > T-table and if the significance <α (0.05), then H0 is rejected, then in the calculation of the coefficient of determination it is known that the effect of office layout on teacher performance at MP UIN Jakarta is 38.2% while the remaining 61.8% is influenced by other factors not examined. However, it can be suggested for the madrasah pay more attention to the arrangement and area of office space for the freedom of teachers to move. As well as paying attention to what needs are needed by teachers so that teachers can improve the quality and performance of their teaching.